'I didn't realise I was such a sausage': men's accounts of whole-body scanning, body image, and expected changes in health-related behaviours. Issue 5 (4th May 2019) - Grogan, Sarah; O'Brien, Daisy; Brownbridge, Kathryn; Gill, Simeon; Cole, Jenny; Armitage, Christopher J.
Abstract: Objective: Whole-body scanning is now available in stores to assist buyers in choosing well-fitting clothes. This study was designed to investigate men's accounts of scanning, body image and expectations of behaviour change. Design: Ten men aged 18–39 years without histories of eating disorders or previous experience of whole-body scanning, took part in semi-structured interviews before and after scanning. Data were analysed using inductive thematic analysis. Results: Pre-scan, men's body ideals were tall, slender and relatively muscular. Post-scan, seven reported looking shorter, fatter, thinner and/or less symmetrical than they hoped; three were pleasantly surprised by the images. Men were interested in scans as an objective view of their bodies and as a 'wake-up call' to motivate healthy behaviours. Five men intended to change their behaviour as a result of scanning, and repeat scanning was seen as a good way to monitor behavioural changes. Participants suggested that scanning may raise body concerns in other men, though downplayed impacts on their own body image. Conclusion: Whole-body scanning may encourage men to exercise and eat more healthily. However, men became more negative about their bodies as a result of seeing their body scans, so scanning needs to be carried out with supervision and support.